Особливості дотримання прав людини в умовах надзвичайних правових режимів, спричинених пандемією - Расторгуєва, Н. О.; Rastorhuieva, N. O.; ORCID: http://orcid.org/0000-0002-1234-2767 (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 48-57, 2022)
Досліджено пандемію як юридичну передумову запровадження певних механізмів дотримання прав людини в умовах надзвичайних правових режимів та виокремлено певні особливості дотримання і гарантування цих прав. Проаналізовано вітчизняні та закордонні нормативно-правові акти стосовно підстав запровадження надзвичайних правових режимів. Звернено увагу на механізми запобігання обмеженням прав людини під час запровадження надзвичайних правових режимів. Визначено ознаки надзвичайного стану та наведено нормативні засади введення цього стану в Україні. Запропоновано на нормативному рівні чітко закріпити перелік конституційних прав і свобод, які можуть бути обмежені, та підстав такого обмеження.

The article is devoted to the study of the pandemic as a legal prerequisite for the introduction of certain mechanisms for the observance of human rights in the conditions of emergency legal regimes and to the identification of certain features of the observance and guarantee of these rights. A number of domestic and foreign legal acts regulating the introduction of the state of emergency have been analyzed. The main purpose of introducing a state of emergency has been determined. The list of reasons for restricting human rights has been analyzed and attention has been drawn to international experience in preventing this negative phenomenon. It has been noted that each state operates with a sufficient amount of information in order to determine the level of public danger and thereby answer the question: if it is appropriate to limit human rights. State authorities within their competence are authorized to make decisions regarding the scope and nature of human rights restriction. The state, assessing a certain emergency situation, must do it correctly from the danger of the situation point of view and taking into account the relevant factors (whether there is public danger that threatens the life of the nation), if necessary, declare a state of emergency to combat it. A classification of legal regimes has been carried out, which include extraordinary and hybrid ones. It has been noted that the main difference between them lies in the constitutionalization of the first ones, which provide for a rather significant retreat of the state from ensuring a number of human and citizen rights and freedoms. Attention has been focused on the fact that, since a state of emergency can lead to the restriction of human rights, it is necessary to turn to the international experience of preventing this negative phenomenon. There are three main tools that human rights law uses to deal with emergencies: human rights exceptions; restriction of human rights; derogation of rights. Taking into account the peculiarities of the emergency situation, it is possible to limit thescope of human rights necessary to overcome the emergency situation, however, at the regulatory level, the list of constitutional rights and freedoms that may be limited and on what grounds should be clearly established.

Исследована пандемия как юридическая предпосылка для внедрения определенных механизмов соблюдения прав человека в условиях чрезвычайных правовых режимов и выделены определенные особенности соблюдения и гарантирования этих прав. Проанализированы отечественные и зарубежные нормативно правовые акты относительно оснований введения чрезвычайных правовых режимов. Обращено внимание на механизмы предотвращения ограничений прав человека при введении чрезвычайных правовых режимов. Определены признаки чрезвычайного положения и нормативные основы введения этого состояния в Украине. Предложено на нормативном уровне четко закрепить перечень конституционных прав и свобод, которые могут быть ограничены и оснований такого ограничения.
Peculiarities of observing human rights in the conditions of emergency legal regimes caused by the pandemic
Расторгуєва, Н. О. Особливості дотримання прав людини в умовах надзвичайних правових режимів, спричинених пандемією / Наталія Олегівна Расторгуєва // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 48-57. - DOI: https://doi.org/10.32631/v.2022.3.04.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; права людини; human right; права человека; пандемія; pandemic; пандемия; надзвичайний стан; state of emergency; черезвычайное положение; правовий режим; legal regime; правовой режим; законодавство; legislation; законодательство; держава; state; государство